Synthesis of Dinaphthofuranofuran and Dinaphthopyranopyran Derivatives - (:unkn) unknown (Freund Publishing House Ltd, 2000)
Condensation reaction of carbonyl compounds [ glyoxal, 1,3-dihydroxyacetone and 1,3-bis-(hydroxymethyl) acetone ] with hydroxyaromatic compounds have been carried out and the structures of the products have been investigated. Naphthofuranonaphthofuran is modified by adding the functional groups which have been chosen from the compounds used for cancer and AIDS chemotherapy.